Polyolefin Compositions Having Improved Electrical Properties - Patent application
A curable composition of polyolefin, fumed alumina, and UV stabilizer enhances the electrical properties of non-Ziegler-Natta catalyzed polyolefins, addressing the VR and DF limitations, enabling their use in electrical applications.
Patent Information
- Application Number
- JP2022513422
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-30
- Filing Date
- 2020-08-26
- Publication Date
- 2025-01-06
- Estimated Expiration
- 2040-08-26
AI Technical Summary
Non-Ziegler-Natta catalyzed polyolefins exhibit lower volume resistivity (VR) and higher dissipation factor (DF) compared to Ziegler-Natta catalyzed polyolefins, limiting their use in applications requiring high VR and low DF for improved electrochemical degradation resistance and reduced electrical losses.
A curable composition comprising a polyolefin, fumed alumina, a silane compound, and a UV stabilizer, optionally with a crosslinking agent and additives, which when cured, significantly enhances the VR and reduces the DF of non-Ziegler-Natta catalyzed polyolefins.
The composition achieves a substantial increase in VR by at least an order of magnitude and a reduction in DF, making non-Ziegler-Natta catalyzed polyolefins suitable for electrical applications.
Smart Images

Figure 0007608441000001 
Figure 0007608441000002 
Figure 0007608441000003
Abstract
Description
[Technical field]
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of International Patent Application No. PCT / CN2019 / 103783, filed August 30, 2019, which is incorporated by reference in its entirety. [Background technology]
[0002] Excellent electrical properties are required for polyolefins in various applications such as wire and cable, electrical accessories, hoses, automotive weather strip applications, etc. These applications require polyolefins with high volume resistivity (VR) and low dissipation factor (DF) as these properties are generally understood to help improve electrochemical degradation (ECD) resistance and reduce electrical losses.
[0003] Polyolefins can be produced through different catalyst systems such as Ziegler-Natta (ZN) or non-Ziegler-Natta (non-ZN) catalyst systems. ZN catalyst systems are the conventional technology and have low catalytic efficiency, requiring high catalyst loadings and a de-ashing step for purification. Non-ZN catalyst systems have a very high efficiency and do not require de-ashing, which greatly improves productivity and significantly reduces production costs. In addition to this, polyolefins produced through non-ZN catalysts have a more uniform composition and improved properties.
[0004] However, in terms of electrical properties, ZN-catalyzed polyolefins may perform better than non-ZN-catalyzed polyolefins. For example, in terms of VR and DF (electrical loss), ZN-catalyzed EPDM performs much better than EPDM produced through non-ZN catalysts. Therefore, there is a need to improve the VR and DF properties of non-ZN-catalyzed polyolefin compositions for electrical applications so that the advantages of non-ZN-catalyzed systems can be brought to such applications. Summary of the Invention
[0005] In certain embodiments, the present disclosure relates to a curable composition comprising (A) a polyolefin, (B) a fumed alumina, (C) a silane compound, and (D) a UV stabilizer. Optionally, the curable composition may further comprise other components, such as (E) a crosslinker, (F) a crosslinking coagent, and / or (G) an additive component.
[0006] In a further embodiment, the present disclosure relates to a crosslinked polymer composition that is a reaction product of a curable composition comprising (A) a polyolefin, (B) a fumed alumina, (C) a silane compound, and (D) a UV stabilizer. Optionally, the curable composition may further comprise other components, such as (E) a crosslinker, (F) a crosslinking coagent, and / or (G) an additive component.
[0007] definition All references herein to the Periodic Table of the Elements shall refer to the Periodic Table of the Elements published and copyrighted in 2003 by CRC Press, Inc., and any reference to a Group(s) shall be to the Group(s) reflected in that Periodic Table of the Elements using the IUPAC system for numbering the Groups.
[0008] For purposes of United States patent practice, the contents of any referenced patents, patent applications, or publications are incorporated by reference in their entirety (or the equivalent United States version thereof is so incorporated by reference), particularly with respect to the disclosure of definitions (to the extent not inconsistent with any definitions specifically provided in this disclosure) and general knowledge in the art.
[0009] Numerical ranges disclosed herein include all values (boundaries) from the lower limit to the upper limit, and ranges including explicit values (e.g., from 1, or 2, or 3 to 5, or 6, or 7) include all subranges between any two explicit values (e.g., 1-2, 2-6, 5-7, 3-7, 5-6, etc.).
[0010] Unless stated to the contrary, implicit from the context, or customary in the art, all parts and percentages are by weight and all test methods are current as of the filing date of this disclosure.
[0011] The term "composition," as used herein, refers to a mixture of materials that comprise the composition, as well as reaction products and decomposition products formed from the materials of the composition.
[0012] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not they are specifically disclosed herein. For the avoidance of doubt, all compositions claimed through the use of the term "comprising" may include any additional additives, adjuvants, or compounds (whether polymeric or non-polymeric), unless stated to the contrary. In contrast, the term "consisting essentially of" excludes from the scope of any succeeding recitation any other components, steps, or procedures, except those that are not essential to operability. The term "consisting of" excludes any component, step, or procedure not expressly delineated or listed. The term "or" refers to the recited members individually as well as in any combination, unless otherwise stated. The use of the singular includes the use of the plural, and vice versa.
[0013] The term "polymer" refers to a material prepared by reacting (i.e., polymerizing) a set of monomers, which may be a homogeneous (i.e., only one type) set of monomers or a heterogeneous (i.e., two or more types) set of monomers. As used herein, the term polymer includes the term "homopolymer," which refers to a polymer prepared from a homogeneous set of monomers, and the term "interpolymer," which is defined below.
[0014] The term "interpolymer" refers to a polymer prepared by polymerization of at least two different types of monomers. The term includes both "copolymers", i.e., polymers prepared from two different types of monomers, and polymers prepared from three or more different types of monomers, e.g., terpolymers, tetrapolymers, etc. The term also encompasses all forms of interpolymers, such as random, block, uniform, heterogeneous, etc.
[0015] As used herein, the term "ethylene / alpha-olefin interpolymer" refers to a polymer that comprises in polymerized form a majority weight percent of ethylene (based on the weight of the interpolymer) and at least one comonomer that is an alpha-olefin. Ethylene / alpha-olefin interpolymers can be random or block interpolymers. The terms "ethylene / alpha-olefin copolymer" and "ethylene / alpha-olefin multi-block interpolymer" are encompassed by the term "ethylene / alpha-olefin interpolymer."
[0016] As used herein, the term "ethylene / alpha-olefin copolymer" refers to a copolymer that contains, in polymerized form, a majority weight percent of ethylene (based on the weight of the copolymer), and a comonomer that is an alpha-olefin, where ethylene and the alpha-olefin are the only two monomer types. Ethylene / alpha-olefin copolymers can be random or block copolymers.
[0017] As used herein, "ethylene / alpha-olefin multi-block interpolymer" or "olefin block copolymer" refers to an interpolymer comprising ethylene and one or more copolymerizable alpha-olefin comonomers in polymerized form, characterized by a plurality of blocks or segments of two or more (preferably three or more) polymerized monomer units, the blocks or segments differing in chemical or physical properties. Specifically, the term refers to a polymer comprising two or more (preferably three or more) chemically distinct regions or segments (referred to as "blocks") linked in a linear fashion, i.e., chemically distinct units that are linked end-to-end (covalently bonded) with respect to polymerized functional groups, rather than in a pendant or grafted fashion. The blocks differ in the amount or type of comonomer incorporated therein, density, amount of crystallinity, type of crystallinity (e.g., polyethylene vs. polypropylene), size of crystals resulting from polymers of such composition, type or degree of stereoregularity (isotactic or syndiotactic), regioregularity or regioirregularity, amount of branching, including long chain branching or hyperbranching, uniformity, and / or any other chemical or physical property. The block copolymers are characterized by unique distributions in both polymer molecular weight distribution (PDI or Mw / Mn) and block length distribution, for example, based on the effectiveness of the use of a shuttling agent in combination with the catalyst system. Non-limiting examples of the olefin block copolymers of the present disclosure, as well as processes for preparing them, are disclosed in U.S. Patent Nos. 7,858,706 B2, 8,198,374 B2, 8,318,864 B2, 8,609,779 B2, 8,710,143 B2, 8,785,551 B2, and 9,243,090 B2, all of which are incorporated herein by reference in their entirety.
[0018] As used herein, the term "ethylene / alpha-olefin / diene interpolymer" refers to a polymer comprising, in polymerized form, ethylene, an alpha-olefin, and a diene. In one embodiment, the "ethylene / alpha-olefin / diene interpolymer" comprises a majority weight percent ethylene (based on the weight of the interpolymer).
[0019] As used herein, the term "propylene / alpha-olefin interpolymer" refers to a polymer that comprises, in polymerized form, a majority weight percent of propylene (based on the weight of the interpolymer) and at least one comonomer that is an alpha-olefin (wherein ethylene is considered an alpha-olefin). The propylene / alpha-olefin interpolymer can be a random or block interpolymer. The term "propylene / alpha-olefin interpolymer" includes the term "propylene / alpha-olefin copolymer."
[0020] As used herein, the term "propylene / alpha-olefin copolymer" refers to a copolymer that includes, in polymerized form, a majority weight percent of propylene (based on the weight of the copolymer) and a comonomer that is an alpha-olefin, where propylene and the alpha-olefin are the only two monomer types. The propylene / alpha-olefin copolymer can be a random or block copolymer.
[0021] A "polyolefin" is a polymer made from the polymerization of olefins as monomers, where the olefin monomers are linear, branched, or cyclic compounds of carbon and hydrogen having at least one double bond. Thus, as used herein, the term "polyolefin" includes and encompasses the terms "ethylene / alpha-olefin interpolymer", "ethylene / alpha-olefin copolymer", "ethylene / alpha-olefin multiblock interpolymer", "ethylene / alpha-olefin / diene interpolymer", "propylene / alpha-olefin interpolymer", and "propylene / alpha-olefin copolymer".
[0022] As used herein, the term "Ziegler-Natta catalyst" refers to a vanadium-based catalyst. As used herein, "Ziegler-Natta catalyzed polymer" or similar term refers to a polymer having a vanadium content greater than 0.4 ppm according to the methods disclosed herein or similar methods.
[0023] As used herein, the term "non-Ziegler-Natta catalyzed" refers to Group 4 metal-based catalysts, including those known in the art such as metallocene catalysts, constrained geometry complex (CGC) catalysts, post-metallocene catalysts, molecular catalysts, and advanced molecular catalysts. As used herein, "non-Ziegler-Natta catalyzed polymers" and similar terms refer to polymers having a Group 4 metal content of 0.3 ppm or more, according to the methods disclosed herein or similar methods. "Non-Ziegler-Natta catalyzed polymers" may also have a vanadium content of 0.4 ppm or less, according to the methods disclosed herein or similar methods.
[0024] Test Method Each of the characteristics described in this disclosure is in accordance with the following methodology.
[0025] Mooney Viscosity: Mooney viscosity is measured with a Mooney shear disc viscometer according to ASTM 1646. The instrument is an Alpha Technologies Mooney Viscometer 2000. The torque to rotate the rotor at 2 rpm is measured by a torque transducer. After closing the platen, the sample is preheated for 1 minute. The motor is then started and the torque is recorded for 4 minutes. The results are reported in Mooney Units (MU) as "ML(1+4) at 125°C". The term "ML" indicates that a large rotor "Mooney Large" is used in the viscosity test, which is the standard size rotor. Mooney Viscosity (MV) measures the resistance of a polymer to flow at relatively low shear rates and is an indication of the polymer's flowability.
[0026] Density: Measure density according to ASTM D792, Method B. Report the results in grams per cubic centimeter (g / cc or g / cm 3 ) to record.
[0027] Monomer Content: The ethylene and propylene contents of the interpolymers as weight percent are determined by Fourier Transform Infrared (FTIR) analysis according to ASTM D3900. The diene (ENB) content of the interpolymers as weight percent is determined by Fourier Transform Infrared (FTIR) analysis according to ASTM D6047.
[0028] Residual Elemental Analysis: Residual elemental analysis to determine the metal content (e.g., vanadium content, group 4 metal content, titanium content, hafnium content, and / or zirconium content) of the interpolymer is performed using inductively coupled plasma atomic emission spectroscopy (ICP-AES) technique. For ICP-AES analysis, the sample is weighed into a quartz tube and 1 mL of water and 3 mL of nitric acid are added to the sample. The sample is placed in a 115°C hot block for 30 minutes. The sample is then placed in an UltraWave microwave oven and digested at 250°C. After microwave digestion, the sample is diluted and analyzed for aluminum, calcium, chromium, titanium, and vanadium on a Perkin Elmer ICP. Results are reported in parts per million (ppm).
[0029] Gel Permeation Chromatography ("GPC"): The chromatography system consisted of a PolymerChar GPC-IR (Valencia, Spain) high temperature GPC chromatograph equipped with an internal IR5 infrared detector (IR5). The autosampler oven compartment was set at 160 degrees Celsius, and the column compartment was set at 150 degrees Celsius. The columns used were four Agilent "Mixed A" 30 cm 20 micron linear mixed bed columns and a 20 um precolumn. The chromatography solvent used was 1,2,4-trichlorobenzene, which contained 200 ppm of butylated hydroxytoluene (BHT). The solvent source was nitrogen sparged. The injection volume used was 200 microliters, and the flow rate was 1.0 milliliters / minute.
[0030] Calibration of the GPC column set was performed with 21 narrow molecular weight distribution polystyrene standards with molecular weights ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures with at least 10-fold spacing between individual molecular weights. Standards were purchased from Agilent Technologies. Polystyrene standards were prepared at 0.025 grams in 50 milliliters of solvent for molecular weights equal to or greater than 1,000,000, and 0.05 grams in 50 milliliters of solvent for molecular weights less than 1,000,000. The polystyrene standards were dissolved at 80 degrees Celsius for 30 minutes with gentle agitation. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (described in Williams and Ward, J. Polym. Sci., Polym. Let., 6, 621 (1968)):
number
[0031] A fifth order polynomial was used to fit each of the polyethylene equivalent calibration points. A small adjustment (approximately 0.375 to 0.445) was made to A to correct for column resolution and band broadening effects for a linear homopolymer polyethylene standard obtained at 120,000 Mw.
[0032] Total plate counts for the GPC column set were performed in decane (prepared at 0.04 g in 50 milliliters of TCB and dissolved for 20 minutes with gentle agitation). Plate counts (Equation 2) and symmetry (Equation 3) were measured with a 200 microliter injection according to the following equations:
number
number
[0033] Samples were prepared in a semi-automated fashion using the PolymerChar "Instrument Control" software to target sample weights of 2 mg / ml and add solvent (containing 200 ppm BHT) via the PolymerChar high temperature autosampler to pre-nitrogen sparged septa-capped vials. Samples were dissolved at 160 degrees Celsius with "slow" shaking for 2 hours.
[0034] Mn (GPC) , Mw (GPC) , and Mz (GPC) The calculations were made based on the GPC results using the PolymerChar GPCOne™ software, the baseline-subtracted IR chromatogram at each equally spaced data collection point (i), and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) in Equation 1, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph according to Equations 4-6.
number
[0035] To monitor deviations over time, a flow marker (decane) was introduced into each sample via a micropump controlled by the PolymerChar GPC-IR system. This flow marker (FM) was used to linearly correct the pump flow rate (Flow (apparent)) of each sample by aligning the RV of the respective decane peak in the sample (RV (FM sample)) with that of the decane peak in the narrow standard calibration (RV (FM calibrated)). Any change in time of the decane marker peak is thus assumed to be related to a linear shift in flow rate (Flow (effective)) throughout the run. To facilitate the highest accuracy of the RV measurement of the flow marker peak, a least squares fitting routine is used to fit the peaks of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation is then used to determine the true peak position. After calibrating the system based on the flow marker peaks, the effective flow rate (relative to the narrow standard calibration) is calculated as in Equation 7. Processing of the flow marker peaks was performed by PolymerChar GPCOne™ software. Acceptable flow correction should be within + / - 1% of the apparent flow rate for effective flow. Flow Rate(effective) = Flow Rate(nominal) * (RV(calibrated FM) / RV(sample FM)) (Equation 7)
[0036] Volume Resistivity: Volume resistivity is determined by the following method based on ASTM D257. Volume resistivity is determined using a Keithley 6517 B electrometer in combination with a Keithley 8009 test accessory. The Keithley model 8009 test chamber is located within a forced air oven capable of operating at high temperatures (maximum temperature 80° C.). Leakage current is recorded from the instrument via software and volume resistivity (VR) is calculated using the following equation:
number
[0037] Dissipation factor (DF): The dissipation factor was measured using the cured film. The film thickness was about 0.8 mm. The cured film samples were degassed at 70°C for 24 hours before the measurement. The measurement was carried out at 90°C, a stress level of 2 kV / mm and 50 Hz. A YG9187 high-precision high-voltage capacitance bridge from Shanghai Young Electrical Co.,Ltd was used for the measurement. The measurement was in accordance with GB / T 1409-2006. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0038] Polyolefin The (A) polyolefin of the present disclosure can be any interpolymer in which an olefin is the major monomer. That is, the polyolefin can be an interpolymer that includes a majority of polymerized units derived from an olefin monomer, and the interpolymer further includes units derived from a comonomer that is a C2-C30 linear, branched, or cyclic alpha-olefin, different from the olefin monomer. For the purposes of this disclosure, ethylene is an alpha-olefin. Non-limiting examples of C2-C30 alpha-olefins for use as comonomers include ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene.
[0039] In certain embodiments, the polyolefin is an ethylene / alpha-olefin interpolymer. Non-limiting examples of ethylene / alpha-olefin interpolymers include interpolymers of ethylene and C3-C8 alpha-olefins, or C4-C8 alpha-olefins, such as ethylene / propylene interpolymers, ethylene / 1-butene interpolymers, ethylene / 1-hexene interpolymers, ethylene / 1-octene interpolymers, and combinations thereof.
[0040] In certain embodiments, the polyolefin is an ethylene / alpha-olefin copolymer. Non-limiting examples of ethylene / alpha-olefin copolymers include copolymers of ethylene and C3-C8 alpha-olefins, or C4-C8 alpha-olefins, such as ethylene / propylene copolymers, ethylene / 1-butene copolymers, ethylene / 1-hexene copolymers, ethylene / 1-octene copolymers, and combinations thereof.
[0041] In certain embodiments, the polyolefin is an ethylene / alpha-olefin / diene interpolymer, as discussed further below.
[0042] In a further embodiment, the polyolefin is an ethylene / alpha-olefin multi-block interpolymer or an olefin block copolymer as defined herein.
[0043] In certain embodiments, the polyolefin is a propylene / alpha-olefin interpolymer. Non-limiting examples of propylene / alpha-olefin interpolymers include propylene / ethylene interpolymer, propylene / 1-butene interpolymer, propylene / 1-hexene interpolymer, propylene / 1-octene interpolymer, and combinations thereof. In further embodiments, the polyolefin is a propylene / alpha-olefin copolymer. Non-limiting examples of propylene / alpha-olefin copolymers include propylene / ethylene copolymer, propylene / 1-butene copolymer, propylene / 1-hexene copolymer, propylene / 1-octene copolymer, and combinations thereof.
[0044] In certain embodiments, the polyolefin is free of heteroatoms. The term "heteroatom" as used herein is an atom other than carbon or hydrogen. Heteroatoms can be non-carbon atoms from groups IV, V, VI, and VII of the periodic table. Non-limiting examples of heteroatoms include F, N, O, P, B, S, and Si.
[0045] In certain embodiments, the polyolefin has a vanadium content (or includes an amount of vanadium) of 0.4 ppm or less or 0.3 ppm or less according to the method disclosed herein or a similar method. In further embodiments, the polyolefin has a Group 4 metal content (or includes an amount of Group 4 metal) of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more according to the method disclosed herein or a similar method. In further embodiments, the polyolefin has a vanadium content (or includes an amount of vanadium) of 0.4 ppm or less or 0.3 ppm or less and / or a Group 4 metal content (or includes an amount of Group 4 metal) of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more.
[0046] In further embodiments, the polyolefin has one, some, or all of the following: a Mooney viscosity (ML 1+4 at 125° C.) according to ASTM D1646 of greater than 0 to 100 MU, or from 5 to 100 MU; a density according to ASTM D792, Method B of from 0.850 g / cc to 0.920 g / cc; from 40% to 80% by weight, or from 50% to 80% by weight, polymerized ethylene; 0 to 10% by weight, polymerized diene; and a molecular weight distribution (MWD or Mw / Mn) of 1 to 7, or from 1 to 5, or from 2 to 4.
[0047] In certain embodiments, the polyolefin has a density according to ASTM D792, Method B, from 0.850 g / cc to 0.920 g / cc, or from 0.860 g / cc to 0.910 g / cc, or from 0.860 g / cc to 0.900 g / cc, or from 0.860 g / cc to 0.890 g / cc.
[0048] In some embodiments, the polyolefin has a melt index according to ASTM D1238 at 190° C. / 2.16 kg of 0.1 to 1,000 dg / min, or 0.1 to 500 dg / min, or 0.1 to 100 dg / min, or 0.1 to 75 dg / min, or 0.1 to 50 dg / min, or 0.1 to 25 dg / min, or 0.5 to 15 dg / min, or 1 to 10 dg / min.
[0049] In some embodiments, the polyolefin has a melt flow rate at 230° C. / 2.16 kg of 0.1-1,000 dg / min, or 0.1-500 dg / min, or 0.1-100 dg / min, or 0.1-75 dg / min, or 0.1-50 dg / min, or 0.1-25 dg / min, or 0.5-15 dg / min, or 1-10 dg / min according to ASTM D1238. Suitable polyolefins include, but are not limited to, those available under the trade names NORDEL™, ENGAGE™, INFUSE™, and VERSIFY™ from The Dow Chemical Company, Exact™ and Vistamaxx™ from ExxonMobil Chemical Company, and LUCENE™ from LG Chemical.
[0050] The polyolefin may have any combination of the embodiments described herein.
[0051] Ethylene / Alpha-Olefin / Diene Interpolymer In an embodiment in which the (A) polyolefin of the present disclosure is an ethylene / alpha-olefin / diene interpolymer, the ethylene / alpha-olefin / diene interpolymer comprises ethylene, an alpha-olefin, and a diene in polymerized form. The diene may be conjugated or non-conjugated. Suitable examples of the alpha-olefin include C3-C20 alpha-olefins or C3-C10 alpha-olefins. Suitable examples of the diene include C4-C40 non-conjugated dienes.
[0052] The alpha-olefin can be either aliphatic or aromatic. In some embodiments, the alpha-olefin is a C3-C10 aliphatic alpha-olefin. In some embodiments, the alpha-olefin is selected from the group consisting of propylene, 1-butene, 1-hexene, and 1-octene. In certain embodiments, the alpha-olefin is propylene.
[0053] In certain embodiments, the diene is a non-conjugated diene that is acyclic or cyclic. Non-limiting examples of non-conjugated dienes include straight-chain acyclic dienes such as 1,4-hexadiene, 1,5-heptadiene, and 1,9-decadiene; branched-chain acyclic dienes such as 5-methyl-1,4-hexadiene, 2-methyl-1,5-hexadiene, 6-methyl-1,5-heptadiene, 7-methyl-1,6-octadiene, 3,7-dimethyl-1,6-octadiene, 3,7-dimethyl-1,7-octadiene, 5,7-dimethyl-1,7-octadiene, and mixed isomers of dihydromyrcene; 1,4-cyclohexadiene, 1,5-cyclooctadiene, and 1,5-cyclohexadiene. Monocyclic alicyclic dienes such as clododecadiene; polycyclic alicyclic fused and bridged ring dienes such as tetrahydroindene and methyltetrahydroindene; alkenyl, alkylidene, cycloalkenyl, and cycloalkylidene norbornenes such as 5-methylene-2-norbornene (MNB), 5-ethylidene-2-norbornene (ENB), 5-vinyl-2-norbornene, 5-propenyl-2-norbornene, 5-isopropylidene-2-norbornene, 5-(4-cyclopentenyl)-2-norbornene, and 5-cyclohexylidene-2-norbornene. In a further embodiment, the diene is a non-conjugated diene selected from the group consisting of ENB, dicyclopentadiene, 1,4-hexadiene, and 7-methyl-1,6-octadiene. In a further embodiment, the diene is ENB.
[0054] In some embodiments, the ethylene / alpha-olefin / diene interpolymer is an ethylene / propylene / diene (EPDM) interpolymer. In further embodiments, the ethylene / alpha-olefin / diene interpolymer is an ethylene / propylene / diene (EPDM) interpolymer, and the diene is ENB.
[0055] In some embodiments, the ethylene / alpha-olefin / diene interpolymers are prepared using non-Ziegler-Natta catalysts, such as CGC catalysts, advanced molecular catalysts, or post-metallocene catalysts. Examples of such catalysts include, but are not limited to, those disclosed in U.S. Pat. Nos. 5,272,236, 5,278,272, and 8,101,696, as well as U.S. Patent Publication No. 2005 / 0164872, and International Patent Publication No. 2007 / 136494, each of which is fully incorporated herein by reference.
[0056] In some embodiments, the ethylene / alpha-olefin / diene interpolymer has a Mooney viscosity (ML1+4 at 125° C.) according to ASTM D1646 of greater than 0 to 100 MU, or from 5 to 100 MU. In certain embodiments, the ethylene / alpha-olefin / diene interpolymer has a Mooney viscosity (ML1+4 at 125° C.) according to ASTM D1646 of 5 MU, or 10 MU, or 15 MU, or 18 MU, or 20 MU, or 25 MU, or 30 MU, or 35 MU to 40 MU, or 45 MU, or 50 MU, or 55 MU, or 60 MU, or 65 MU, or 70 MU, or 75 MU, or 80 MU, or 85 MU, or 90 MU, or 99 MU, or 100 MU.
[0057] In further embodiments, the ethylene / alpha-olefin / diene interpolymer has a Mooney viscosity (ML1+4 at 125° C.) according to ASTM D1646 of greater than 0 to 100 MU, or from 5 MU to 100 MU, or from 15 MU to 100 MU, or from 15 MU to 99 MU, or from 15 MU to 90 MU, or from 15 MU to 80 MU, or from 15 MU to 70 MU, or from 15 MU to 60 MU, or from 15 MU to 50 MU, or from 18 MU to 45 MU, or from 18 MU to 40 MU.
[0058] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer has a density according to ASTM D792, Method B of 0.850 g / cc, or 0.860 g / cc, or 0.870 g / cc to 0.880 g / cc, or 0.890 g / cc, or 0.900 g / cc, or 0.910 g / cc, or 0.920 g / cc. In further embodiments, the ethylene / alpha-olefin / diene interpolymer has a density according to ASTM D792, Method B of 0.850 g / cc to 0.920 g / cc, or 0.860 g / cc to 0.910 g / cc, or 0.860 g / cc to 0.900 g / cc, or 0.860 g / cc to 0.890 g / cc, or 0.860 g / cc to 0.880 g / cc.
[0059] In some embodiments, the ethylene / alpha-olefin / diene interpolymer comprises a majority of polymerized ethylene based on the weight of the interpolymer. In certain embodiments, the ethylene / alpha-olefin / diene interpolymer comprises 40 wt%, or 45 wt%, or 50 wt%, or 55 wt%, or 60 wt%, or 68 wt% to 70 wt%, or 71 wt%, or 75 wt%, or 80 wt%, or 85 wt% polymerized ethylene. In further embodiments, the ethylene / alpha-olefin / diene interpolymer comprises 40 to 80 wt%, or 50 to 80 wt%, or 55 to 70 wt% polymerized ethylene.
[0060] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer comprises greater than 0 wt%, or 0.5 wt%, or 1 wt%, or 2 wt%, or 3 wt%, or 3.5 wt%, or 4 wt%, or 4.5 wt%, or 4.7 wt% to 4.9 wt%, or 5 wt%, or 6 wt%, or 7 wt%, or 7.5 wt%, or 8 wt%, or 8.5 wt%, or 9 wt%, or 10 wt%, of polymerized diene, based on the weight of the interpolymer. In further embodiments, the ethylene / alpha-olefin / diene interpolymer comprises greater than 0 to 10 wt%, or 0.5 wt% to 9 wt%, or 0.5 wt% to 8.5 wt%, of polymerized diene, such as ENB.
[0061] In some embodiments, the ethylene / alpha-olefin / diene interpolymer has a molecular weight distribution (MWD or Mw / Mn) from 1 to 7, or from 1 to 5, or from 1.5 to 5, or from 2 to 4.
[0062] The ethylene / alpha-olefin / diene interpolymers may have the following metal contents according to the methods disclosed herein or similar methods: In certain embodiments, the ethylene / alpha-olefin / diene interpolymers have a vanadium content or contain an amount of vanadium of 0.4 ppm or less, or 0.3 ppm or less.
[0063] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer has a titanium content or comprises an amount of titanium of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more.
[0064] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer has a zirconium content or comprises an amount of zirconium that is 0.3 ppm or greater, or 0.4 ppm or greater, or 0.5 ppm or greater, or 0.6 ppm or greater.
[0065] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer has a hafnium content or comprises an amount of hafnium of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more.
[0066] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer has a Group 4 metal content or comprises an amount of Group 4 metal of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more.
[0067] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer comprises titanium, zirconium, and / or hafnium in an amount of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more.
[0068] In certain embodiments, the ethylene / alpha-olefin / diene interpolymers have a vanadium content of 0.4 ppm or less, or 0.3 ppm or less, or a Group 4 metal content of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more.
[0069] In certain embodiments, the ethylene / alpha-olefin / diene interpolymer is free of heteroatoms. The term "heteroatom" as used herein is an atom other than carbon or hydrogen. Heteroatoms can be non-carbon atoms from groups IV, V, VI, and VII of the periodic table. Non-limiting examples of heteroatoms include F, N, O, P, B, S, and Si.
[0070] The ethylene / alpha-olefin / diene interpolymers of the present disclosure can include two or more embodiments as described herein or can be any combination of the embodiments as described herein.
[0071] Fumed Alumina The curable composition of the present disclosure further comprises (B) fumed alumina. Fumed alumina (aluminum oxide) is a type of synthetic alumina. As a synthetic alumina, the fumed alumina of the present disclosure has a high degree of chemical purity and a high specific surface area. In a further embodiment, the fumed alumina can be prepared by a flame hydrolysis process known in the art, such as a process similar to the AEROSIL® process. The flame hydrolysis process for preparing fumed alumina can be controlled by varying the concentration of reactants, the flame temperature, and a certain residence time. This affects the particle size, particle size distribution, specific surface area, and surface properties of the fumed alumina product. In other words, depending on how the process is controlled, a variety of fumed alumina products can be made.
[0072] Fumed alumina particles prepared by flame hydrolysis process are inherently hydrophilic unless specially treated. To form hydrophobic fumed alumina particles, the hydrophilic fumed alumina particles are subjected to a chemical post-treatment with a hydrophobic agent. Suitable hydrophobic agents include, but are not limited to, organosilane compounds such as alkoxysilanes, silazanes, and siloxanes. As used herein, the term "hydrophobically treated fumed alumina" refers to fumed alumina in particulate form having a hydrophobic agent bonded to the particle surface by one or more oxygen covalent bonds.
[0073] In certain embodiments, the fumed alumina of the present disclosure is a hydrophilic fumed alumina. In further embodiments, the fumed alumina of the present disclosure is a hydrophobically treated fumed alumina. The fumed alumina of the present disclosure can be in the thermodynamically stable alpha form or the metastable gamma form, including the gamma, delta, and theta forms.
[0074] In one particular embodiment, the fumed alumina is 50 μm 2 / g over ~200m 2In one particular embodiment, the fumed alumina has a specific surface area (BET) of less than 55 m 2 / g~150m 2 / g, or 60m 2 / g~140m 2 / g, or 65m 2 / g~130m 2 In a further embodiment, the fumed alumina has a specific surface area (BET) of 55 m 2 / g, or 60m 2 / g, or 65m 2 / g, or 70m 2 / g, or 75m 2 / g, or 80m 2 / g, or 85m 2 / g~95m 2 / g, or 100m 2 / g, or 105m 2 / g, or 110m 2 / g, or 115m 2 / g, or 120m 2 / g, or 130m 2 / g, or 140m 2 / g, or 150m 2 / g, or 200m 2 / g.
[0075] Non-limiting examples of hydrophilic fumed aluminas are those available from Evonik Industries as AEROXIDE® Alu 65 and Alu 130. A non-limiting example of hydrophobically treated fumed aluminas is that available from Evonik Industries as AEROXIDE® Alu C.
[0076] The fumed alumina of the present disclosure may be a blend of hydrophilic fumed alumina and hydrophobically treated fumed alumina, or may be a blend of more than hydrophilic fumed alumina.
[0077] The fumed alumina of the present disclosure can be any combination of the embodiments disclosed herein.
[0078] Silane Compounds The curable composition of the present disclosure further comprises (C) a silane compound. In certain embodiments, the silane compound is a silane coupling agent containing at least one alkoxy group. Non-limiting examples of suitable silane compounds include γ-chloropropyltrimethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, vinyl-tris-(β-methoxy)silane, allyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, β-(3,4-ethoxy-cyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and 3-(trimethoxysilyl)propyl methacrylate, vinyltriacetoxysilane, γ-(meth)acryloxy, propyltrimethoxysilane, and combinations thereof.
[0079] In some embodiments, the silane compound is vinyltrimethoxysilane (VTMS), or 3-(trimethoxysilyl)propyl methacrylate (VMMS), or allyltrimethoxysilane.
[0080] UV stabilizers The curable composition of the present disclosure further comprises (D) a UV stabilizer. Non-limiting examples of suitable UV stabilizers include hindered phenols, phosphites, hindered amine light stabilizers (HALS), UV absorbers, hindered benzoates, and combinations thereof.
[0081] Suitable UV stabilizers include, but are not limited to, T770 available from TCI; UV 531 available from TCI; Cynergy A400, A430 and R350; Cyasorb UV-3529; Cyasorb UV-3346; Cyasorb UV-3583; Hostavin N30; Univil 4050; Univin 5050; Chimassorb UV-119; Chimassorb 944 LD; Tinuvin 622 LD; benzophenones, benzotriazoles, triazines, and combinations thereof, such as Tinuvin 328 or Cyasorb UV-1164.
[0082] In certain embodiments, the UV stabilizer is a hindered amine light stabilizer.
[0083] Crosslinking Agent The curable composition of the present disclosure can be cured to form a crosslinked polymer composition. The crosslinked polymer composition is a reaction product of the curable composition resulting from curing. Thus, in certain embodiments, the curable composition further comprises (E) a crosslinker.
[0084] Non-limiting examples of suitable crosslinking agents include peroxides; phenols; azides; aldehyde-amine reaction products; substituted ureas; substituted guanidines; substituted xanthates; substituted dithiocarbamates; sulfur-containing compounds such as thiazoles, sulfenamides, thiuramidisulfides, paraquinone dioxime, dibenzoparaquinone dioxime, sulfur; imidazoles; silanes; metal oxides such as zinc, magnesium, and lead oxides; dinitroso compounds such as p-quinone-dioxime and p,p'-dibenzoylquinone-dioxime; and phenol-formaldehyde resins containing hydroxymethyl or halomethyl functional groups, and combinations thereof.
[0085] Suitable crosslinkers include those based on sulfur, such as elemental sulfur. When sulfur-based curing agents are used, the following curing agents may be used: amines, disulfides, guanidines, thioureas, thiazoles, thiurams, sulfenamides, dithiocarbamates, xanthates, 4,4'-dithiodimorpholine, thiuram di- and polysulfides, alkylphenol disulfides, and 2-morpholino-dithiobenzothiazole, tetramethylthiuram disulfide (TMTD), dipentamethylenethiuram tetrasulfide (DPTT), 2-mercapto ... Accelerators and cure activators such as zinc 2-mercaptobenzothiazolate disulfide (MBT), 2-mercaptobenzothiazolate disulfide (MBTS), zinc 2-mercaptobenzothiazolate (ZMBT), zinc diethyldithiocarbamate zinc (ZDEC), zinc dibutyldithiocarbamate (ZDBC), dipentamethylene thiuram tetrasulfide (DPTT), Nt-butylbenzothiazole-2-sulfanamide (TBBS), and mixtures thereof may be used as well.
[0086] Additional crosslinkers include, but are not limited to, phenolic resins, azides, aldehyde-amine reaction products, vinyl silanes, hydrosilylating agents, substituted ureas, substituted guanidines, substituted xanthates, substituted dithiocarbamates, and combinations thereof. The crosslinker may be a phenolic or peroxide curing agent with an optional coagent, or a hydrosilation crosslinking agent with a hydrosilation catalyst, or dibutyltin dilaurate ("DBTDL") with the optional coagent alumina trihydrate ("ATH"). Common industrial catalysts are "Speier's catalyst", which is HPtCl6, and Karstedt's catalyst, which is an alkene-stabilized platinum(0) catalyst.
[0087] In a preferred embodiment, the crosslinker may include one or more organic peroxides, including but not limited to alkyl peroxides, aryl peroxides, ester peroxides, peroxycarbonates, diacyl peroxides, ketal peroxides, cyclic peroxides, dialkyl peroxides, ester peroxides, peroxydicarbonates, or combinations of two or more thereof. Examples of peroxides include but are not limited to di-tert-butyl peroxide, dicumyl peroxide, di(3,3,5-trimethylhexanoyl)peroxide, t-butyl peroxypivalate, t-butyl peroxyneodecanoate, di(sec-butyl)peroxydicarbonate, t-amyl peroxyneodecanoate, 1,1-di-t-butylperoxy-3,3,5-trimethylcyclohexane, t-butyl-cumyl peroxide, 2,5-dimethyl-2,5-di(tert-butyl-peroxy)hexane, 1,3-bis(tert-butyl-peroxyl-isopropyl)benzene, or combinations thereof. An exemplary crosslinking agent is dicumyl peroxide, commercially available under the trade name LUPEROX® from Arkema, or TRIGONOX® from Akzo Nobel. A further exemplary crosslinking agent is VAROX® DBPH-50 from Vanderbilt Chemicals. When the crosslinking agent is a peroxide, certain processing aids and cure activators, such as stearic acid and ZnO, can also be used.
[0088] Further examples of suitable organic peroxides include dicumyl peroxide, lauryl peroxide, benzoyl peroxide, tertiary butyl perbenzoate, di(tertiary butyl) peroxide, cumene hydroperoxide, 2,5-dimethyl-2,5-di(t-butyl-peroxy)hexyne-3, 2,-5-dimethyl-2,5-di(t-butyl-peroxy)hexane, tertiary butyl hydroperoxide, isopropyl percarbonate, alpha,alpha'-bis(tertiary butylperoxy)diisopropylbenzene, t-butylperoxy-2-ethylhexyl-monocarbonate, 1,1-bis(t-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethyl-2,5-dihydroxyperoxide, t-butylcumyl peroxide, alpha,alpha'-bis(t-butylperoxy)-p-diisopropylbenzene, bis(1,1-dimethylethyl) peroxide, bis(1,1-dimethylpropyl) peroxide, 2,5-Dimethyl-2,5-bis(1,1-dimethylethylperoxy)hexane, 2,5-Dimethyl-2,5-bis(1,1- 4,4-Bis(1,1-dimethylethylperoxy)valeric acid, butyl ester, 1,1- Bis(1,1-dimethylethylperoxy)-3,3,5-trimethylcyclohexane, benzoyl peroxide, tert-butyl perbenzoate, Peroxybenzoic acid, di-tert-amyl peroxide ("DTAP"), bis(alpha-t-butyl-peroxyisopropyl)benzene ("BIPB"), isopropyl cumyl t-butyl peroxide, t-butyl cumyl peroxide, di-t-butyl peroxide, 2,5-bis(t-butylperoxy)-2,5-dimethylhexane, 2,5-bis(t-butylperoxy)-2,5-dimethylhexyne-3,1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-di(t-amylperoxy)-2,5-dimethylhexane, isopropyl These include, but are not limited to, propyl cumyl peroxide, butyl 4,4-di(tertbutylperoxy)valerate, di(isopropylcumyl)peroxide, 2,5-di-(t-butylperoxy)-2,5-diphenylhexane, bis(alpha-methylbenzyl)peroxide, benzoyl peroxide, t-butyl perbenzoate, 3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxonane, bis(t-butylperoxy)-diisopropylbenzene, di-2-t-butylperoxyisopropylbenzene, and combinations thereof.
[0089] Non-limiting examples of suitable commercially available organic peroxides include those available from AkzoNobel under the trade name TRIGONOX® and those available from Arkema under the trade name LUPEROX®, such as LUPEROX® F40P.
[0090] As discussed further below, when a peroxide-based curing agent is used, a co-activator or coagent may be used in combination with the peroxide-based curing agent. Suitable coagents include, but are not limited to, trimethylolpropane triacrylate (TMPTA), trimethylolpropane trimethacrylate (TMPTMA), triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), and 1,4-phenylenedimaleimide (available from TCI Chemicals).
[0091] When a crosslinking agent is used, crosslinking can be induced by activating the crosslinking agent in the curable composition. The crosslinking agent can be activated by exposing the crosslinking agent to a temperature above its decomposition temperature. The temperature range is 50°C to 300°C, for example 80°C to 275°C. The time can be determined by one skilled in the art depending on the selected polymer and curing components.
[0092] Alternatively, the crosslinking agent can be activated by exposing it to radiation that causes the production of free radicals from the crosslinking agent. Non-limiting examples of suitable radiation include UV or visible light, electron beam, or beta, gamma, X-ray, or neutron radiation. It is believed that the radiation activates crosslinking by generating radicals in the polymer that can then bond and crosslink. The amount of radiation depends on many factors and can be determined by those skilled in the art. When the crosslinking agent is a peroxide photoinitiator, such as dibenzoyl peroxide, cumene hydroperoxide, di-t-butyl peroxide, diacetyl peroxide, hydrogen peroxide, peroxy disulfate, and 2,2-bis(terbutylperoxy)-2,5-dimethylhexane, UV or visible light activation can occur.
[0093] In some embodiments, a dual cure system comprising at least two activation methods, such as a combination selected from heat, moisture cure, and radiation, may be effectively used. For example, it may be desirable to use a peroxide crosslinker with a silane crosslinker, a peroxide crosslinker with radiation, a sulfur-containing crosslinker with a silane crosslinker, etc. One skilled in the art will be able to readily select the amount of crosslinker based on the desired level of crosslinking, the characteristics of the polymer, such as molecular weight, molecular weight distribution, comonomer content, the presence of crosslinking promoters, other additives, etc.
[0094] Crosslinking agent In certain embodiments where the curable composition of the present disclosure includes a peroxide crosslinker, the curable composition may further include (F) a crosslinking coagent. The crosslinking coagent may be any one or a mixture of coagents including, but not limited to, aliphatic or aromatic ethers containing at least two, preferably three, unsaturated groups such as esters, ethers, ketones, cyanurates, isocyanurates, phosphates, orthoformates, allyls, vinyls, or acrylates. The number of carbon atoms in the crosslinking coagent may range from 9 to 40 or more, preferably 9 to 20.
[0095] Specific examples of auxiliaries include trimethylolpropane trimethacrylate (TRIM), triallyl cyanurate (TAC), triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione, also known as triallyl isocyanurate (TAIC), hexaallyl melamine, triallyl phosphate (TAP), triallyl orthoformate, tetra-allyloxy-ethane, triallylbenzene-1,3,5-tricarboxylate, diallyl phthalate, diallyl terephthalate, zinc dimethacrylate, ethoxylated bisphenol A dimethacrylate, methacrylate-terminated monomers having an average chain length of C14 or C15, pentaerythritol tetraacrylate, depentaerythritol pentaacrylate, pentaerythritol triacrylate, dimethylolpropane tetra ... These include, but are not limited to, silated trimethylolpropane triacrylate, trimethylolpropane triacrylate, 2,4,6-triallyl-1,3,5-trione, 2,4-diphentyl-4-methyl-1-pentene, triallyl trimellitate (TATM), 3,9-divinyl-2,4,8,10-tetra-oxaspiro[5.5]undecane (DVS), alpha-methylstyrene dimer (AMSD), 1,2 polybutadiene, divinylbenzene, trimethylolpropane trimethacrylate, polyethylene glycol dimethacrylate, ethylene glycol dimethacrylate, allyl methacrylate, N,N'-m-phenylene bismaleimide, toluene bismaleimide-p-quinone dioxime, nitrobenzene, diphenyl guanidine, and combinations thereof.
[0096] In certain embodiments, the crosslinking coagent may be selected from the group consisting of TRIM, TAIC, TAC, TAP, vinyl cyclic siloxanes, and combinations thereof.
[0097] Additive Ingredients The curable composition of the present disclosure may include one or more additives. Thus, the curable composition may include (G) additive component. Suitable additives that may constitute the additive component include, but are not limited to, metal oxides, antioxidants, fillers, UV stabilizers, flame retardants, plasticizers or oils, colorants or pigments, tackifiers, reinforcing agents, fatty acids and their salts, ignition resistance additives, scorch inhibitors, stabilizers, foaming agents, lubricants, processing aids, extrusion aids, nucleating agents, scavengers, waxes, curing additives, accelerators, and combinations thereof.
[0098] Metal oxides include, but are not limited to, oxides of silicon, calcium, zinc, iron, titanium, and aluminum. Fillers include, but are not limited to, carbon black; silicates of aluminum, magnesium, calcium, sodium, potassium, and mixtures thereof; carbonates of calcium, magnesium, and mixtures thereof; sulfates of calcium, barium, and lead; alumina trihydrate; magnesium hydroxide; phenol-formaldehyde, polystyrene, and poly(alphamethyl)-styrene resins, natural fibers, synthetic fibers, and the like.
[0099] Plasticizers or oils include, but are not limited to, petroleum oils such as aromatic and naphthenic oils; polyalkylbenzene oils; organic acid monoesters such as alkyl and alkoxyalkyl oleates and stearates; organic acid diesters such as dialkyl, dialkoxyalkyl and alkylaryl phthalates, terephthalates, sebacates, adipates and glutarates; glycol diesters such as tri-, tetra- and polyethylene glycol dialkanoates; trialkyl trimellitates; trialkyl, trialkoxyalkyl, alkyl diaryl and triaryl phosphates; chlorinated paraffin oils; coumarone-indene resins; pine tar; vegetable oils such as castor oil, tall oil, rapeseed oil and soybean oil, and their esters and epoxidized derivatives.
[0100] Antioxidants and antiozonants include hindered phenols, bisphenols, and thiobisphenols; substituted hydroquinones; tris(alkylphenyl)phosphites; dialkylthiodipropionates; phenylnaphthylamines; substituted diphenylamines; dialkyl, alkylaryl, and diaryl substituted p-phenylenediamines; monomeric and polymeric dihydroquinolines; 2-(4-hydroxy-3,5-t-butylaniline)-4,6-bis(octylthio)1,3,5-triazine, hexahydro b-1,3,5-tris-β-(3,5-di-t-butyl-4-hydroxyphenyl)propionyl-s-triazine, 2,4,6-tris(n-1,4-dimethylpentylphenylene-diamino)-1,3,5-triazine, tris-(3,5-di-t-butyl-4-hydroxybenzyl)isocyanurate, nickel dibutyldithiocarbamate, 2-mercaptotolylimidazole and its zinc salt, petroleum wax, 2,2,4-trimethyl-1,2-dihydroquinoline, and the like.
[0101] curable composition The present disclosure relates to a curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) a silane compound; and (D) a UV stabilizer. Optionally, the curable composition may further comprise (E) a crosslinker, (F) a crosslinking coagent, and / or (G) an additive component.
[0102] The (A) polyolefin may be present in the curable composition in an amount of 80% to 99.99% by weight, or 84% to 99.97% by weight, or 90% to 99.97% by weight, or 95% to 99.97% by weight, based on the total weight of the curable composition.
[0103] (B) The fumed alumina may be present in the hardenable composition in an amount of 0.01 wt.% to 5 wt.%, or 0.1 wt.% to 3 wt.%, or 0.5 wt.% to 2 wt.%, or 0.5 wt.% to 1 wt.%, based on the total weight of the hardenable composition.
[0104] The (C) silane compound may be present in the curable composition in an amount of 0.01 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.1 wt % to 2 wt %, based on the total weight of the curable composition.
[0105] (D) The UV stabilizer may be present in the curable composition in an amount of 0.01 wt.% to 5 wt.%, or 0.01 wt.% to 3 wt.%, or 0.01 wt.% to 1 wt.%, based on the total weight of the curable composition.
[0106] The (E) crosslinker may be present in the curable composition in an amount of 0 wt.% to 5 wt.%, or 0.01 wt.% to 5 wt.%, or 0.5 wt.% to 5 wt.%, or 1 wt.% to 3 wt.%, based on the total weight of the curable composition.
[0107] The (F) crosslinking coagent may be present in the curable composition in an amount of 0 wt. % to 5 wt. %, or 0.01 wt. % to 5 wt. %, or 0.05 wt. % to 3 wt. %, or 0.1 wt. % to 1 wt. %, based on the total weight of the curable composition.
[0108] The (G) additive component may be present in the curable composition in an amount of 0 wt.% to 10 wt.%, or 0.01 wt.% to 10 wt.%, or 0.05 wt.% to 8 wt.%, or 0.1 wt.% to 5 wt.%, or 0.5 wt.% to 3 wt.%, based on the total weight of the curable composition.
[0109] (A) The polyolefins can be blended with one or more polymers. Thus, the curable compositions of the present disclosure (as well as crosslinked polymer compositions including the reaction products of the curable compositions) can further include one or more polymers, including, but not limited to, unsaturated polyolefins (another EPDM, polybutadiene, etc.), saturated polyolefins (PE, PP, ethylene / alpha-olefin interpolymers, propylene / alpha-olefin interpolymers, olefin block copolymers, etc.), other elastomers (SBC, PVC, EVA, etc.), and other engineering thermoplastics (styrene, polyamides, polyesters, etc.).
[0110] In certain embodiments, the polyolefin is not blended with other polymers. In certain embodiments, the curable composition is free of (or does not consist of) any polymer other than (A) the polyolefin.
[0111] The curable compositions of the present disclosure may be cured to form crosslinked polymer compositions. The crosslinked polymer compositions of the present disclosure are the reaction products of the curable compositions.
[0112] The curable composition or crosslinked polymer composition, according to the methods disclosed herein or similar methods, may have the following properties, volume resistivity at room temperature: In certain embodiments, the curable composition or crosslinked polymer composition has a volume resistivity of greater than 1.0E+15 ohm.cm, or greater than 5.0E+15 ohm.cm, or greater than 1.0E+16 ohm.cm, or 2.5E+16 ohm.cm or greater, or 5.0E+16 ohm.cm or greater, or 6.0E+16 ohm.cm or greater, or 8.0E+16 ohm.cm or greater, or 1.0E+17 ohm.cm or greater, or 1.30E+17 ohm.cm or greater, or 3.0E+17 ohm.cm or greater, or 5.0E+17 ohm.cm or greater, or 1.0E+18 ohm.cm or greater, or 5.0E+18 ohm.cm or greater, or 1.0E+19 ohm.cm or greater.
[0113] In certain embodiments, the curable composition or crosslinked polymer composition has a volume resistivity of greater than 1.0E+15 ohm.cm to 1.0E+19 ohm.cm, or greater than 1.0E+15 ohm.cm to 5.0E+18 ohm.cm, or greater than 1.0E+15 ohm.cm to 1.0E+18 ohm.cm, or greater than 1.0E+15 ohm.cm to 5.0E+17 ohm.cm, or greater than 1.0E+15 ohm.cm to 4.0E+17 ohm.cm, or greater than 1.0E+15 ohm.cm to 3.0E+17 ohm.cm, or greater than 5.0E+15 ohm.cm to 2.0E+17 ohm.cm, or greater than 1.0E+16 ohm.cm to 2.0E+17 ohm.cm.
[0114] In some embodiments, the curable composition or crosslinked polymer composition, according to a method disclosed herein or a similar method, has a dielectric tangent of 0 to less than 10, or less than 8, or less than 6, or less than 4, or less than 2, or 1 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.16 or less, or 0.15 or less, or 0.1 or less, or 0.078 or less.
[0115] Each of the curable composition and the crosslinked polymer composition may have any combination of the embodiments described herein.
[0116] Articles and uses The curable composition or crosslinked polymer composition of the present disclosure can be used to make articles by any one of many conventional processes and equipment.Exemplary processes include, but are not limited to, extrusion, calendaring, compression molding, and other typical thermosetting material forming processes.For example, articles can be made by extrusion, additional heat treatment after extrusion, low pressure molding, compression molding, etc.
[0117] The articles made with the curable composition or crosslinked polymer composition of the present disclosure include, but are not limited to, sheets, films, molded articles, fibers, and extruded parts.Additional articles include, but are not limited to, soft-touch goods, automotive parts, adhesives, piping, weather stripping, belts, hoses, architectural profiles, wire and cable jackets and components, flooring, gaskets and profiles, tires and tire components, computer parts, building materials, coatings, woodwork, photovoltaic articles, and footwear components.Those skilled in the art can easily extend this list without undue experimentation.
[0118] Articles may have the following VR properties according to the methods disclosed herein and similar methods: In certain embodiments, articles made from (or including) the curable or crosslinked polymeric compositions have a volume resistivity of greater than 1.0E+15 ohm.cm, or greater than 5.0E+15 ohm.cm, or greater than 1.0E+16 ohm.cm, or 2.5E+16 ohm.cm or greater, or 5.0E+16 ohm.cm or greater, or 6.0E+16 ohm.cm or greater, or 8.0E+16 ohm.cm or greater, or 1.0E+17 ohm.cm or greater, or 1.30E+17 ohm.cm or greater, or 3.0E+17 ohm.cm or greater, or 5.0E+17 ohm.cm or greater, or 1.0E+18 ohm.cm or greater, or 5.0E+18 ohm.cm or greater, or 1.0E+19 ohm.cm or greater.
[0119] In certain embodiments, an article made from (or including) the curable composition or the crosslinked polymer composition has a volume resistivity of greater than 1.0E+15 ohm.cm to 1.0E+19 ohm.cm, or greater than 1.0E+15 ohm.cm to 5.0E+18 ohm.cm, or greater than 1.0E+15 ohm.cm to 1.0E+18 ohm.cm, or greater than 1.0E+15 ohm.cm to 4.0E+17 ohm.cm, or greater than 1.0E+15 ohm.cm to 5.0E+17 ohm.cm, or greater than 1.0E+15 ohm.cm to 3.0E+17 ohm.cm, greater than 5.0E+15 ohm.cm to 2.0E+17 ohm.cm, or greater than 1.0E+16 ohm.cm to 2.0E+17 ohm.cm.
[0120] In some embodiments, an article made from (or including) the curable composition or the crosslinked polymer composition has a dielectric tangent of 0 to less than 10, or less than 8, or less than 6, or less than 4, or less than 2, or 1 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.16 or less, or 0.15 or less, or 0.1 or less, or 0.078 or less.
[0121] Specific embodiments of the present disclosure include, but are not limited to, the following. 1. A curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) a silane compound; and (D) a UV stabilizer. 2. The curable composition of embodiment 1, further comprising (E) a crosslinker. 3. The curable composition of embodiment 1 or 2, further comprising (F) a crosslinking coagent and / or (G) an additive component. 4. (A) 80% to 99.99% by weight, or 84% to 99.97% by weight, or 90% to 99.97% by weight, or 95% to 99.97% by weight of a polyolefin, based on the total weight of the curable composition; (B) from 0.01 wt. % to 5 wt. %, or from 0.1 wt. % to 3 wt. %, or from 0.5 wt. % to 2 wt. %, or from 0.5 wt. % to 1 wt. % of fumed alumina, based on the total weight of the curable composition; (C) 0.01 wt % to 5 wt %, or 0.1 wt % to 3 wt %, or 0.1 wt % to 2 wt %, of a silane compound, based on the total weight of the curable composition; and (D) from 0.01 wt % to 5 wt %, or from 0.01 wt % to 3 wt %, or from 0.01 wt % to 1 wt %, of a UV stabilizer, based on the total weight of the curable composition; and (E) from 0 wt. % to 5 wt. %, or from 0.01 wt. % to 5 wt. %, or from 0.1 wt. % to 5 wt. %, or from 1 wt. % to 3 wt. %, of a crosslinker, based on the total weight of the curable composition; and (F) 0 wt % to 5 wt %, or 0.01 wt % to 5 wt %, or 0.05 wt % to 3 wt %, or 0.1 wt % to 1 wt %, of a crosslinking coagent, based on the total weight of the curable composition; (G) from 0 wt. % to 10 wt. %, or from 0.01 wt. % to 10 wt. %, or from 0.05 wt. % to 8 wt. %, or from 0.1 wt. % to 5 wt. %, or from 0.5 wt. % to 3 wt. %, based on the total weight of the curable composition, of an additive component. 5. The curable composition of any one of the preceding embodiments, wherein the polyolefin is selected from the group consisting of ethylene / alpha-olefin / diene interpolymers, ethylene / alpha-olefin copolymers, propylene / alpha-olefin copolymers, and ethylene / alpha-olefin multi-block interpolymers. 6. The curable composition of any one of the preceding embodiments, wherein the alpha-olefin is selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-tetradecene, 1-hexadecene, and 1-octadecene. 7. The curable composition of any one of the preceding embodiments, wherein the polyolefin is an ethylene / alpha-olefin / diene interpolymer. 8. The curable composition of any one of the preceding embodiments, wherein the polyolefin is an ethylene / propylene / diene interpolymer. 9. The curable composition of any one of the preceding embodiments, wherein the polyolefin is an ethylene / propylene / ENB interpolymer. 10. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises vanadium in an amount of 0.4 ppm or less, or 0.3 ppm or less. 11. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises a Group 4 metal in an amount of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more. 12. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises titanium in an amount of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more. 13. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises zirconium in an amount of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more. 14. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises hafnium in an amount of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more. 15. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises titanium, zirconium, and / or hafnium in an amount of 0.3 ppm or more, or 0.4 ppm or more, or 0.5 ppm or more, or 0.6 ppm or more. 16. The curable composition of any one of the preceding embodiments, wherein the polyolefin has a Mooney viscosity (ML1+4 at 125° C.) according to ASTM D1646 of greater than 0 to 100 MU, or from 5 MU to 100 MU, or from 15 MU to 100 MU, or from 15 MU to 99 MU, or from 15 MU to 90 MU, or from 15 MU to 80 MU, or from 15 MU to 70 MU, or from 15 MU to 60 MU, or from 15 MU to 50 MU, or from 18 MU to 45 MU, or from 18 MU to 40 MU. 17. Polyolefin is Density from 0.850 g / cc to 0.920 g / cc, or from 0.860 g / cc to 0.910 g / cc, or from 0.860 g / cc to 0.900 g / cc, or from 0.860 g / cc to 0.890 g / cc, or from 0.860 g / cc to 0.880 g / cc, according to ASTM D792, Method B; A melt index in accordance with ASTM D1238 of 0.1 to 1,000 dg / min, or 0.1 to 500 dg / min, or 0.1 to 100 dg / min, or 0.1 to 75 dg / min, or 0.1 to 50 dg / min, or 0.1 to 25 dg / min, or 0.5 to 15 dg / min, or 1 to 10 dg / min at 190°C / 2.16 kg; and / or 2. The curable composition of any one of the preceding embodiments, having a melt flow rate according to ASTM D1238 at 230° C. / 2.16 kg of 0.1 to 1,000 dg / min, or 0.1 to 500 dg / min, or 0.1 to 100 dg / min, or 0.1 to 75 dg / min, or 0.1 to 50 dg / min, or 0.1 to 25 dg / min, or 0.5 to 15 dg / min, or 1 to 10 dg / min. 18. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises 40 to 80% by weight, or 50 to 80% by weight, or 55 to 70% by weight of polymerized ethylene. 19. The curable composition of any one of the preceding embodiments, wherein the polyolefin comprises 0 to 10 wt.%, or 0.5 wt.% to 9 wt.%, or 0.5 wt.% to 8.5 wt.% of polymerized diene. 20. The curable composition of any one of the preceding embodiments, wherein the polyolefin has a molecular weight distribution (MWD or Mw / Mn) of 1-7, or 1-5, or 1.5-5, or 2-4. 21. The curable composition of any one of the preceding embodiments, wherein the fumed alumina is hydrophilic. 22. Fumed alumina is 50m 2 / g over ~200m 2 / g or less than 55m 2 / g~150m 2 / g, or 60m 2 / g~140m 2 / g, or 65m 2 / g~130m 2 The curable composition of any one of the preceding embodiments, having a specific surface area (BET) of 100 / g. 23. The curable composition of any one of the preceding embodiments, wherein the silane compound is selected from the group consisting of vinyltrimethoxysilane (VTMS), 3-(trimethoxysilyl)propyl methacrylate (VMMS), and allyltrimethoxysilane. 24. The curable composition of any one of the preceding embodiments, wherein the UV stabilizer is a hindered amine light stabilizer. 25. The curable composition of any one of embodiments 2 to 24, wherein the crosslinking agent is an organic peroxide. 26. The curable composition of any one of the preceding embodiments, wherein the curable composition has a volume resistivity of greater than 1.0E+15 ohm.cm, or greater than 5.0E+15 ohm.cm, or greater than 1.0E+16 ohm.cm, or 2.5E+16 ohm.cm or greater, or 5.0E+16 ohm.cm or greater, or 6.0E+16 ohm.cm or greater, or 8.0E+16 ohm.cm or greater, or 1.0E+17 ohm.cm or greater, or 1.30E+17 ohm.cm or greater, or 3.0E+17 ohm.cm or greater, or 5.0E+17 ohm.cm or greater, or 1.0E+18 ohm.cm or greater, or 5.0E+18 ohm.cm or greater, or 1.0E+19 ohm.cm or greater. 27. The curable composition of any one of the preceding embodiments, wherein the curable composition has a volume resistivity of greater than 1.0E+15ohm.cm to 1.0E+19ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 4.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 3.0E+17ohm.cm, or greater than 5.0E+15ohm.cm to 2.0E+17ohm.cm, or greater than 1.0E+16ohm.cm to 2.0E+17ohm.cm. 28. The curable composition of any one of the preceding embodiments, wherein the curable composition has a dielectric tangent of 0 to less than 10, or less than 8, or less than 6, or less than 4, or less than 2, or 1 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.16 or less, or 0.15 or less, or 0.1 or less, or 0.078 or less. 29. A crosslinked polymer composition comprising a curable composition according to any one of the preceding embodiments. 30. A crosslinked polymer composition that is the reaction product of the curable composition of any one of embodiments 1-28. 31. A crosslinked polymer composition comprising the reaction product of a curable composition according to any one of embodiments 1-28. 32. The crosslinked polymer composition of any one of embodiments 29-31, wherein the crosslinked polymer composition has a volume resistivity greater than 1.0E+15 ohm.cm, or greater than 5.0E+15 ohm.cm, or greater than 1.0E+16 ohm.cm, or 2.5E+16 ohm.cm or greater, or 5.0E+16 ohm.cm or greater, or 6.0E+16 ohm.cm or greater, or 8.0E+16 ohm.cm or greater, or 1.0E+17 ohm.cm or greater, or 1.30E+17 ohm.cm or greater, or 3.0E+17 ohm.cm or greater, or 5.0E+17 ohm.cm or greater, or 1.0E+18 ohm.cm or greater, or 5.0E+18 ohm.cm or greater, or 1.0E+19 ohm.cm or greater. 33. The crosslinked polymer composition of any one of embodiments 29-32, wherein the crosslinked polymer composition has a volume resistivity of greater than 1.0E+15ohm.cm to 1.0E+19ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 3.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 4.0E+17ohm.cm, or greater than 5.0E+15ohm.cm to 2.0E+17ohm.cm, or greater than 1.0E+16ohm.cm to 2.0E+17ohm.cm. 34. The crosslinked polymer composition of any one of embodiments 29-33, wherein the crosslinked polymer composition has a dielectric tangent of 0 to less than 10, or less than 8, or less than 6, or less than 4, or less than 2, or 1 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.16 or less, or 0.15 or less, or 0.1 or less, or 0.078 or less. 35. An article comprising the curable composition of any one of embodiments 1 to 28. 36. An article made from the curable composition of any one of embodiments 1 to 28. 37. An article comprising the crosslinked polymer composition of any one of embodiments 29-34. 38. An article made from the crosslinked polymer composition according to any one of embodiments 29 to 34. 39. The article of any one of embodiments 35-38, wherein the article has a volume resistivity greater than 1.0E+15 ohm.cm, or greater than 5.0E+15 ohm.cm, or greater than 1.0E+16 ohm.cm, or 2.5E+16 ohm.cm or greater, or 5.0E+16 ohm.cm or greater, or 6.0E+16 ohm.cm or greater, or 8.0E+16 ohm.cm or greater, or 1.0E+17 ohm.cm or greater, or 1.30E+17 ohm.cm or greater, or 3.0E+17 ohm.cm or greater, or 5.0E+17 ohm.cm or greater, or 1.0E+18 ohm.cm or greater, or 5.0E+18 ohm.cm or greater, or 1.0E+19 ohm.cm or greater. 40. The article of any one of embodiments 35-39, wherein the article has a volume resistivity of greater than 1.0E+15ohm.cm to 1.0E+19ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 1.0E+18ohm.cm, or greater than 1.0E+15ohm.cm to 5.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 3.0E+17ohm.cm, or greater than 1.0E+15ohm.cm to 4.0E+17ohm.cm, or greater than 5.0E+15ohm.cm to 2.0E+17ohm.cm, or greater than 1.0E+16ohm.cm to 2.0E+17ohm.cm. 41. The article of any one of embodiments 35-40, wherein the article has a dielectric tangent of 0 to less than 10, or less than 8, or less than 6, or less than 4, or less than 2, or 1 or less, or 0.7 or less, or 0.6 or less, or 0.5 or less, or 0.4 or less, or 0.3 or less, or 0.2 or less, or 0.16 or less, or 0.15 or less, or 0.1 or less, or 0.078 or less. 42. The article of any one of embodiments 35-41, wherein the article is a film. EXAMPLES
[0122] material The materials used in the following examples are described below.
[0123] NORDEL™ 4725P (“EPDM1”): an ethylene propylene diene interpolymer available from The Dow Chemical Company (produced via a non-ZN catalyst): has a density of 0.880 g / cc (ASTM D792); Mooney viscosity (ML1+4 at 125° C.) of 25 MU (ASTM D1646); ethylene content of 68 / 70 wt.% (ASTM D3900); and ENB content of 4.9 wt.% (ASTM D6047).
[0124] NORDEL™ 3720P ("EPDM2"): an ethylene propylene diene interpolymer (produced via a non-ZN catalyst) available from The Dow Chemical Company: has a density of 0.880 g / cc (ASTM D792); Mooney viscosity (ML 1+4 at 125°C) of 20 MU (ASTM D1646); ethylene content of 70 wt% (ASTM D3900); and ENB content of 0.5 / 0.6 wt% (ASTM D6047).
[0125] NORDEL™ 6530 XFC (“EPDM3”): an ethylene propylene diene interpolymer (produced via a non-ZN catalyst) available from The Dow Chemical Company: has a density of 0.880 g / cc (ASTM D792); Mooney viscosity (ML 1+4 at 125° C.) of 30 MU (ASTM D1646); ethylene content of 55 wt.% (ASTM D3900); and ENB content of 8.5 wt.% (ASTM D6047).
[0126] INFUSE™ 9530 (“OBC”): an ethylene / alpha-olefin multiblock interpolymer or olefin block copolymer (produced via a non-ZN catalyst) available from The Dow Chemical Company: has a density of 0.887 g / cc (ASTM D792), and a melt index of 5 dg / min (ASTM D1238) at 190° C. / 2.16 kg.
[0127] ENGAGE™ 8200 (“POE1”): an ethylene / 1-octene copolymer (produced via a non-ZN catalyst) available from The Dow Chemical Company: has a density of 0.870 g / cc (ASTM D792), and a melt index of 5 dg / min (ASTM D1238) at 190° C. / 2.16 kg.
[0128] VERSIFY™ 2300 (“POE2”): A propylene / ethylene copolymer (produced via a non-ZN catalyst) available from The Dow Chemical Company: has a density of 0.867 g / cc (ASTM D792), and a melt flow rate of 2 dg / min at 230° C. / 2.16 kg (ASTM D1238).
[0129] "Alumina": Fumed alumina available as Aeroxide® Alu 130 from Evonik Industries.
[0130] "VMMS": 3-(trimethoxysilyl)propyl methacrylate.
[0131] "VTMS": vinyltrimethoxysilane.
[0132] "HALS 1": Bis(2,2,6,6-tetramethyl-4-piperidyl) sebacate, a hindered amine light stabilizer available as 770 from TCI.
[0133] "HALS 2": a hindered amine light stabilizer available from BASF as Uvinul® 4050 FF.
[0134] "Peroxide": Dicumyl peroxide available as Luperox® DC from Arkema.
[0135] The residual metal content of the neat resins of EPDM 1-3 was measured according to the methods described herein and is shown in Table 1. "ND" means "not detectable" and indicates a measurement below the detection limit for that metal (0.3 ppm for Zr and 0.4 ppm for V). [Table 1]
[0136] Sample preparation Each of the comparative examples (CE1-CE15) and inventive examples (IE1-IE13) are prepared as described below and according to the formulations in Tables 2-5.
[0137] The polyolefin was fed into the Brabender mixer with a rotor speed of 30 rpm at a set temperature of 100°C. After about 3 minutes, the polyolefin was heated / melted uniformly. After that, all other ingredients including fumed alumina, silane compound, and UV stabilizer were weighed and then gradually added into the chamber. 50 rpm was used for an additional 7 minutes to disperse the fillers and various other additives. For the examples containing peroxide, the rotor speed was reduced and the melt temperature was reduced to below 130°C by using strong cooling before the peroxide was charged into the chamber. Mixing was carried out for an additional 3 minutes to disperse the peroxide. The compound was collected and pressed into a flat pie for further use.
[0138] Preparation of uncured film: The compound from Brabender mixing was preheated at 120°C for 5 minutes, then degassed, followed by a pressing process at 120°C for another 1 minute, and then cooled to room temperature. The film thickness is about 0.8 mm.
[0139] Preparation of cured films: The compounds from the Brabender mix were compression molded into 0.8 mm films. The samples were pre-compressed and first degassed, followed by a pressing process at 180°C for 20 minutes to ensure the samples were fully cured, and then cooled to room temperature.
[0140] Compression molded films were used for VR and DF measurements, as shown in Tables 2-5. [Table 2] [Table 3] [Table 4] [Table 5]
[0141] As seen in Comparative Examples CE1, CE8, and CE9, the VR of polyolefins prepared by non-ZN catalysts is relatively low, in the range of 10 ohm.cm. As seen in Inventive Examples IE1-IE7, the compositions of the present disclosure (comprising polyolefin, fumed alumina, silane compound, and UV stabilizer) surprisingly and unexpectedly increase the VR by a significant amount. When the VR is in the range of 10 ohm.cm, the increase in VR in the Inventive Examples is at least an order of magnitude or more.
[0142] In contrast, as seen in Comparative Examples CE2-CE7, the addition of only one or two of the fumed alumina, silane compound, and UV stabilizer to the polyolefin does not significantly improve VR. Thus, without being bound by any theory, the results surprisingly demonstrate the synergistic effect of the components in the compositions of the present invention to improve VR.
[0143] As seen in Comparative Examples CE10-CE12, the cured polyolefins with peroxide had lower VR and higher DF (electrical loss). Inventive Examples IE8-IE10 show that the inventive compositions of the present disclosure surprisingly and unexpectedly improve VR and DF properties, with the improvement in DF being at least an order of magnitude.
[0144] In summary, the compositions of the present disclosure can significantly improve the electrical properties (higher VR and lower DF) of polyolefins, thereby enabling the use of such polyolefins in electrical-related applications. It should be noted that the present invention includes the following aspects. [Aspect 1] A curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) a silane compound; and (D) a UV stabilizer. [Aspect 2] 2. The curable composition of embodiment 1, further comprising: (E) a crosslinker. [Aspect 3] Based on the total weight of the curable composition, 84% to 99.97% by weight of the polyolefin; 0.01% to 5% by weight of the fumed alumina; 0.01% by weight to 5% by weight of the silane compound; 0.01% to 1% by weight of said UV stabilizer; 3. The curable composition of claim 1 or 2, comprising: [Aspect 4] The curable composition according to any one of aspects [1] to [3], wherein the polyolefin is selected from the group consisting of ethylene / alpha-olefin / diene interpolymers, ethylene / alpha-olefin interpolymers, ethylene / alpha-olefin multiblock interpolymers, and propylene / alpha-olefin interpolymers. [Aspect 5] The curable composition according to any one of [1] to [4], wherein the polyolefin is selected from the group consisting of ethylene / propylene / diene interpolymers, ethylene / 1-octene copolymers, propylene / ethylene copolymers, and ethylene / alpha-olefin multiblock interpolymers. [Aspect 6] The curable composition according to any one of [1] to [5], wherein the polyolefin contains vanadium in an amount of 0.4 ppm or less. [Aspect 7] The curable composition according to any one of [1] to [6], wherein the polyolefin contains a Group 4 metal in an amount of 0.3 ppm or more. [Aspect 8] The curable composition according to any one of [1] to [7], wherein the polyolefin has a Mooney viscosity (ML1+4 at 125°C) according to ASTM D1646 of 5 MU to 100 MU. [Aspect 9] The curable composition according to any one of [1] to [8], wherein the curable composition has a volume resistivity of more than 5.0E+15 ohm.cm. [Aspect 10] A crosslinked polymer composition comprising a reaction product of the curable composition according to any one of [1] to [9]. [Aspect 11] 11. The crosslinked polymer composition of embodiment 10, wherein the crosslinked polymer composition has a volume resistivity greater than 5.0E+15 ohm.cm. [Aspect 12] 12. The crosslinked polymer composition according to any one of claims 10 to 11, wherein the crosslinked polymer composition has a dielectric tangent of less than 2. [Aspect 13] An article comprising the curable composition of any one of embodiments 1-9 or the crosslinked polymer composition of any one of embodiments 10-12. [Aspect 14] 14. The article of claim 13, wherein the article has a volume resistivity greater than 5.0E+15 ohm.cm. [Aspect 15] 15. The article of claim 13 or 14, wherein the article has a dissipation factor of less than 2.
Claims
1. A curable composition comprising: (A) a polyolefin; (B) a fumed alumina; (C) a silane compound; and (D) a UV stabilizer, the polyolefin is selected from the group consisting of ethylene / alpha-olefin / diene interpolymers, ethylene / alpha-olefin interpolymers, ethylene / alpha-olefin multiblock interpolymers, and propylene / alpha-olefin interpolymers; The curable composition, wherein the silane compound is vinyltrimethoxysilane (VTMS), 3-(trimethoxysilyl)propyl methacrylate (VMMS), or allyltrimethoxysilane.
2. The curable composition of claim 1 further comprising (E) a crosslinker.
3. The curable composition of claim 1, wherein the silane compound is VTMS or VMMS.
4. The curable composition of any one of claims 1 to 3, wherein the polyolefin comprises vanadium in an amount of 0.4 ppm or less.
5. The curable composition of any one of claims 1 to 4, wherein the polyolefin comprises a Group 4 metal in an amount of 0.3 ppm or more.
6. 6. The curable composition of any one of claims 1 to 5, wherein the curable composition has a volume resistivity greater than 5.0E+15 ohm.cm.
7. A crosslinked polymer composition comprising the reaction product of the curable composition of any one of claims 1 to 6.
8. 8. The crosslinked polymer composition of claim 7, wherein said crosslinked polymer composition has a volume resistivity greater than 5.0E+15 ohm.cm.
9. 9. The crosslinked polymer composition of claim 7 or 8, wherein the crosslinked polymer composition has a dissipation factor of less than 2.
10. An article comprising the curable composition of any one of claims 1 to 6 or the crosslinked polymer composition of any one of claims 7 to 9.
Citation Information
Patent Citations
Silane crosslinked-polyethylene insulation material adopting one-step method and preparation technology of silane crosslinked-polyethylene insulation material
CN104610634A
POE composite film for packaging photovoltaic module
CN106206790A
Organic / inorganic composite electrolyte and electrochemical device using the same
JP2009527090A
Thermal Interface Material
JP2010538111A
High heat-resistant composition obtained by reaction treatment of polypropylene and olefin interpolymers
JP2011523968A
